Working through trauma in post-dictatorial Chilean documentary: Lorena Giachino's Reinalda del Carmen - Traverso, Antonio (Black Swan Press, 2009)
According to Dominick LaCapra's critique, the Holocause documentary Shoah (1985) would operate in terms of a re-traumatising strategy, appearing obsessed with prompting survivors and other witnesses to act out traumatic symptoms in front of the camera. Alternativelty, LaCapra argues for a favouring of texts that work through trauma and seek to release survivors and audiences from the cycles of trauma transmission. A recent documentary that explores the theme of the military dictatorship that shook Chile betweek 1973 and 1990, Reinalda del Carmen, mi mama y yo (2006) is proposed in this essay as an example of the kind of text favoured by LaCapra. In order to illuminate its analysis of this Chilean documentary of enmeshed personal and public memory this essay draws on the distinction between acting out and working through textual approaches to historical trauma derived from LaCapra's theorisation of this topic. The essay argues that, despite inheriting much of the approach established by Shoah, through its simultaneous articulation of acting-out and working-through strategies Reinalda del Carmen, mi mama y yo moves beyond the limitations identified by LaCapra in Shoah, thus actively contributing to the process of cultural release of the cycle of historical trauma in Chile.